2019
DOI: 10.1136/vr.105528
|View full text |Cite
|
Sign up to set email alerts
|

Controlled field study evaluating the clinical efficacy of a topical formulation containing emodepside and praziquantel in the treatment of natural cat aelurostrongylosis

Abstract: BackgroundAelurostrongylus abstrusus is the most important nematode affecting the respiratory tract of cats in terms of prevalence and clinical relevance. The aim of this randomised controlled field study was to confirm the efficacy of the spot-on containing emodepside/praziquantel (Profender, Bayer Animal Health) in the treatment of aelurostrongylosis.MethodsSeventeen cats with aelurostrongylosis and presenting with clinical and/or radiographic signs were included in the study. Eight cats received two biweekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Fenbendazole is effective in treating aelurostrongylosis if administered at 50 mg/kg of body weight Fenbendazole treatment may require way more than three days of administrations [ 42 ]. A spot-on formulation containing emodepside and praziquantel showed high efficacy against A. abstrusus infection in field conditions [ 43 , 44 ] as well as other spot-on formulations containing either eprinomectin or moxidectin [ 45 ]. Additionally, another effective oral combination was milbemycin oxime and praziquantel administered at 4 mg/kg and 10 mg/kg respectively, three times as a single dose with two-week intervals [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fenbendazole is effective in treating aelurostrongylosis if administered at 50 mg/kg of body weight Fenbendazole treatment may require way more than three days of administrations [ 42 ]. A spot-on formulation containing emodepside and praziquantel showed high efficacy against A. abstrusus infection in field conditions [ 43 , 44 ] as well as other spot-on formulations containing either eprinomectin or moxidectin [ 45 ]. Additionally, another effective oral combination was milbemycin oxime and praziquantel administered at 4 mg/kg and 10 mg/kg respectively, three times as a single dose with two-week intervals [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned molecular tools proved to be powerful in a number of studies, to confirm copromicroscopic diagnoses in clinical cases [ 29 , 41 , 42 , 58 , 60 ], in postmortem evaluations [ 60 , 92 ], in epizootiological and biological surveys [ 2 , 14 , 15 , 20 , 40 , 93 , 94 , 95 , 96 ] and in the clinical evaluations of anthelmintics [ 97 ].…”
Section: Parasitological Diagnosismentioning
confidence: 99%
“…In the same case series [ 26 ], a single dose of a spot-on formulation containing 2.1% emodepside resulted in full clinical recovery and remission of the radiographic alterations in a cat coinfected with A. abstrusus and T. brevior when evaluated 14 days post-treatment. Afterwards, a controlled field study showed high clinical efficacy with two administrations of emodepside, repeated 2 weeks later, in ensuring complete remission of clinical and radiographic signs in eight cats with natural A. abstrusus monospecific infections within 10 weeks of the first administration [ 97 ]. In this latter study, abnormal breath sounds (e.g., crackles) disappeared in around half of the infected cats 14 days after the first administration, while two weeks after the second administration, all study cats did not display clinical signs, with statistically significant differences when compared to the control group [ 97 ].…”
Section: Treatment and Controlmentioning
confidence: 99%
See 2 more Smart Citations